(untitled) (Journal of the College of Basic Education, 2025)
The study aims to assess the effectiveness of the Carousel strategy in enhancing the academic performance of students in the Islamic Education Department in Health Education and fostering their creative thinking skills. The researcher employed an experimental approach with a pretest-posttest design using two equivalent groups (experimental and control) to measure academic achievement and creative thinking. The sample consisted of 53 male and female students from the Islamic Education Department at the College of Basic Education, with the participants randomly assigned to two groups: the experimental group, which was taught using the Carousel strategy (27 students), and the control group, which followed the traditional method (26 students). A 40-item achievement test and an 8-activity creative thinking test were developed. Pilot tests were conducted to ensure the clarity of the items, appropriate response time, and the psychometric properties of the instruments. The results, analyzed using the T-test, indicated that the experimental group outperformed the control group in both the achievement and creative thinking tests. The researcher concluded that the Carousel strategy has a positive effect on improving students’ academic performance and developing their creative thinking. Based on the findings, recommendations and suggestions were made.